Effectivity of Pyridoxine as Adjuvant Therapy of Phenytoin in Patients with Epilepsy at Soebandi Regional Hospital Jember - Yovita Karina Pandan Putri; Cholis Abrori; Komang Yunita Wiryaning Putri (Jember Medical Journal, 2022)
Phenytoin is an antiepileptic drug  used as monotherapy for partial and generalized tonic-clonic seizures for more than 50 years. Pyridoxine is a water-soluble vitamin widely used for seizure patients  unresponsive to standard treatment regimens. This study was conducted to determine the effect of pyridoxine as adjuvant therapy in epilepsy patients receiving phenytoin and to determine the relationship between age, gender, type of epilepsy, and duration of therapy on the incidence of seizures in epilepsy patients at Soebandi Regional Hospital Jember. This research is an observational analytic study with a cross sectional design. The data was taken from the patient's medical record at Soebandi Hospital Jember. The number of samples in each treatment group was 18 samples so the total number of samples in this study was 36 samples. Samples were taken using total sampling technique. Data analysis was performed using Chi-Square  test on bivariate analysis and The Logistic test on multivariate analysis. The sample in this study was dominated by male patients (52.8%), aged 19-59 years (52.8%), had epilepsy with generalized seizure type (86.1%), and received therapy for < 3 years (77.8%). The results of bivariate and multivariate analysis showed correlation between the administration of pyridoxine and the incidence of seizures, indicating that phenytoin therapy with pyridoxine adjuvants was more effective than monotherapy phenytoin. Other factors such as gender, age, type of epilepsy, and duration of therapy were not proven to have a correlation  with the incidence of seizures in epilepsy patients at Soebandi Hospital Jember.